CHARACTERISTICS OF ABORTION INCIDENTS AT ALIYAH II KENDARI HOSPITAL FOR JANUARY - OCTOBER 2023 - Yafie, Zurezki Yuana; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Mortality due pregnancy or delivery difficulties are referred to as maternal mortality. Pregnancy-related hypertension (31.90%), obstetric bleeding (26.90%), non-obstetric problems (18.5%), other obstetric difficulties (11.80%), pregnancy-related infections (4.20%), abortion (5%) and other reasons (1.70%) were the direct causes of maternal death. When the result of conception removed from the uterus when the gestational age of less than 20 weeks or a weight of less than 500 grams, the procedure is known as an abortion. Miscarriage risk is multivariable, Despite the fact that some maternal risk factors are typically more significant than others, no single factor can predict future miscarriage. This article was prepared using descriptive research methods and is secondary research where data was obtained from the medical records section of Aliyah II Hospital in Kendari for the period January October 2023. The conclusion of the study's findings is the majority of patients who had abortions were between the ages of 21 and 34, with an average age of 29.07 years and a range of 17 to 49 years. Patients with multiparity (72,2%) tend to be more numerous than nulliparous (27,8%), while patients with no history of previous abortion (74,8) experience more abortions than patients with a history of abortion (25,2%) in previous pregnancies. Patients who work (44,3%) are less likely to experience abortion when compared to mothers who do not work (55,7%). Key words: Abortion, Maternal Mortality, Risk Factors